Characterization of the Magneto-Optical Trap for Rb Atoms - Liwag, John; Manyaga, Joseph; Patiño, Marlon; Ravacio, Marc; Karremans, Kees (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
A magneto-optical trap (MOT) for rubidium (Rb) atoms has been in operation at the University of San Carlos Optoelectronics Research Laboratory in Cebu City since 1998. The experimental design for this MOT is based on the system described by Wieman et al. (1995). This system formed the backbone of the research which resulted in the first observation of Bose-Einstein condensation (BEC) by the same group in 1995. An essential step for realizing this remarkable result was the accuracy in the timing mechanism of the experiment. To obtain an MOT in which we can switch the laser and magnetic fields with sub-millisecond accuracy, we have put considerable efforts to realize a computer-controlled system. Previous measurements have been used to validate our new results. The realization of a fast switch for the trapping laser creates the opportunity to measure time-of-flight (TOF) signals. These ballistic measurements can be used to infer the temperature of the cloud of trapped atoms. We hope to continue working on this automated system of the MOT towards BEC as a long-term goal of our research group.